Vietnam Journal of Mathematics - Phu, Hoang Xuan.; Anh, Pham Ky.; Hoa, Le Tuan.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Vietnam Journal of Mathematics was originally founded in 1973 by the Vietnam Academy of Science and Technology and the Vietnam Mathematical Society. Published by Springer from 1997 to 2005 and since 2013, this quarterly journal is open to contributions from researchers from all over the world, where all submitted articles are peer-reviewed by experts worldwide. It aims to publish high-quality original research papers and review articles in all active areas of pure and applied mathematics.
Keywords: Mathematics; Mathematics, general